TimeNotes: A Study on Effective Chart Visualization and Interaction Techniques for Time-Series Data - Rita Borgo (IEEE Transactions on Visualization and Computer Graphics, 2015)
Collecting sensor data results in large temporal data sets which need to be visualized, analysed, and presented. One dimensional time-series charts are used, but these present problems when screen resolution is small in comparison to the data. This can result in severe over-plotting, giving rise for the requirement to provide effective rendering and methods to allow interaction with the detailed data. Common solutions can be categorized as multi-scale representations, frequency based, and lens based interaction techniques. In this paper, we comparatively evaluate existing methods, such as Stack Zoom [15] and ChronoLenses [39], giving a graphical overview of each and classifying their ability to explore and interact with data. We propose new visualizations and other extensions to the existing approaches. We undertake and report an empirical study and a field study using these techniques.